Selectivity of agrochemicals on predatory mites (Phytoseiidae) found on coffee plants - Reis, Paulo Rebelles; Franco, Renato André; Neto, Marçal Pedro; Teodoro, Adenir Vieira (Coffee Science - ISSN 1984-3909, 2007)
An evaluation on the effect of agrochemicals to the predatory mites Euseius alatus DeLeon, 1966, Euseius citrifolius Denmark & Muma, 1970, Amblyseius herbicolus (Chant, 1959) and Iphiseiodes zuluagai Denmark & Muma, 1972 (Phytoseiidae) is presented in this paper. These predators are frequently associated to Brevipalpus phoenicis (Geijskes, 1939) (Acari: Tenuipalpidae), vector of the coffee ring spot virus, and to Oligonychus ilicis (McGregor, 1917) (Acari: Tetranychidae) on coffee plants. The residual contact bioassay of spraying in glass surface was used. Twenty-six currently used agrochemicals or those with potential to be used in Brazilian coffee production were tested. Spraying was conducted using a Potter tower at a pressure of 15 lb/pol2; each cover glass received 1.68 ± 0.36 mg/cm2 of the tested products. Adverse effect on the predatory mites was calculated taking into account the mortality of females and the effect in the reproduction during eight days. Tested products were ranked in four toxicity classes according IOBC/WPRS, by the total effect caused to the mite. Five products (fenbutatin oxide, hexythiazox, spiromesifen, spirodiclofen and emamectin) were innocuous or slightly noxious to all predators, whereas three products (abamectin, sulfur and endosulfan) were innocuous or slightly noxious to three of the four predators.